O Estado e a casa patriarcal: caminhos do legalismo nos sertões brasileiros da Primeira República. - João Paulo Mansur (2023)
This work investigates the domestic order of the patriarchal household and its interrelation with the state order in Brazil during the First Republic. The primary historical source under investigation comprises Brazilian regionalist novels, which are juxtaposed, among others, with legal and political doctrines, newspaper articles, legislations, oeconomic works and iconographies. Two methodological reasons prompted the decision to employ literary texts in a legal history of the relationship between the patriarchal household and the State. The modern legalistic culture has delegitimized non-state legal experiences. Therefore, state documents or political-legal doctrines tend to begin their portrayal of the domestic order with the presupposition of its illegality, resulting in a legalistic myopia that overlooks or obscures many of its features. In addition, the regionalist novel has a realistic, and at times memoir-like quality, enabling the disclosure of particularities of a legal order that was rather intimate. The conclusion drawn is that the patriarchal household of the vast land properties acted as a commercial enterprise and a dwelling place for hundreds or thousands of individuals. The internal coexistence was regulated by customary rules, as a territory’s own particular law, operating relatively autonomously in relation to the state legal order. The landlord, akin to a pater familias of that community, was responsible for administering justice among the dwellers. The arbitrary and authoritative role of the patriarchs has been thoroughly investigated by historiography; on the other hand, domestic order, which has played a crucial role in carrying out significant judicial functions, has received insufficient attention. Furthermore, our analysis suggests that the state order and the domestic order had a complex interplay in the First Republic: at times, they coexisted harmoniously or remained indifferent to each other, while in other occasions, they formed pacts of reciprocal support or were engaged in open conflicts. The capture of these relationships will enable us to verify how state power has adjusted to the distant Brazilian hinterlands by implementing strategies that ensured its survival and crafted its future legalist hegemony.